An investigation on titanium doping in reduced graphene oxide by RF magnetron sputtering for dye-sensitized solar cells. (August 2019) - Low, Foo Wah; Lai, Chin Wei; Asim, Nilofar; Akhtaruzzaman, Md.; Alghoul, Mohammad; Tiong, Sieh Kiong; Amin, Nowshad
Highlights: rGO-TiO2 based photoanodes for DSSC were fabricated at different distance in RF sputtering. Crystallinity, particle size, morphology, lattice and chemical state of rGO-TiO2 were investigated. Effects of sputtering distance of Ti 3+ ions onto rGO nano-sheets were elaborated. Best PCE of 6.60% was achieved for 10 cm sputtering distance. Abstract: A study investigating the effects of titanium (Ti) atoms sputtered from different sources on substrate distance was attempted in order to effectively dope a reduced graphene oxide (rGO) thin film surface. Factors such as crystallinity, morphology, phase formation, light absorption, and surface chemical state of rGO-TiO2 were investigated. As a result, functional groups or chemical states revealed the presence of Ti-O-C in rGO-TiO2 nanocomposite after the sputtering process. The titanium source from the target was of Ti 3+ species as determined using X-ray photoelectron spectroscopy (XPS). It was found that average sized Ti 3+ ions of around 59.4 nm were incorporated into the rGO nanosheet. A customized Dye-Sensitized Solar Cells (DSSCs) device was fabricated with the photo-anode consisting of sputtered rGO-TiO2 nanocomposite. After optimization, the Ti target allocated with 10 cm-apart FTO glass-coated rGO nanosheet and 0.67 cm 2 active area exhibited an ideal PCE of 6.60%, which is remarkably higher than the usual 5 cm sputtering distance the sample (1.90%) had achieved.